Evaluation of the effect of cooled EGR on knock of SI engine fueled with alternative gaseous fuels - Chaichan, Miqdam Tariq (Sulaimani Journal for Engineering Sciences, 2014)
The warming of the climate system is unequivocal, as it is now evident from many observations. Most of the climatic warming caused by human activities; include in particular the burning of fossil fuels that generate the 'greenhouse' gases. The transport sector is one of the most important causes of the high levels of air pollution. Alternative gaseous fuels relates to a wide range of fuels that are in the gaseous state at ambient conditions, whether when used on their own or as components of mixtures with other fuels. Exhaust gas recirculation (EGR) is one of the principal techniques used to control spark ignition NOx. However, EGR has different effect on performance, combustion, and emissions production that are difficult to distinguish.The knock characteristics in a single cylinder SI engine were investigated under high load operation and higher useful compression ratio with cooled EGR addition. Liquefied petroleum gases (LPG), natural gas (NG) and hydrogen gas were used as fuels. In this paper, practical analysis has been done to predict the influence of cooled EGR on engine knock by changing some operational and design parameters such as equivalence ratio, spark timing and compression ratio.
Keywords: spark ignition engine; cooled EGR; knock; gasoline; LPG; NG; hydrogen; compression ratio; equivalence ratio; spark timing